The Current Update of ChatGPT Roles in Science Experiment: A Systemic Literature Review - Dewi, Hefi Rusnita; Qudratuddarsi, Hilman; Ningthias, Dyah Puspitasari; Cinthami, Ratih Dhamayyana Dwi (Universitas Sulawesi Barat, 2024)
Scientific experiments provide numerous benefits for school students, including enhancing their understanding of scientific concepts through hands-on experiences. By engaging in experiments, students can develop critical thinking, problem-solving, and data analysis skills. This study aims to analyze the role of ChatGPT in relation to science practicum activities. The study employs a systematic literature review method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Data sources consist of scientific journals that were identified, screened, and evaluated, resulting in only seven journals meeting the inclusion criteria. These journals were then reviewed through thematic analysis to outline the key findings from the analyzed publications. The results show that the majority of the reviewed articles (85.71%) were published in the Journal of Chemical Education, with a focus on the field of chemistry (85.71%), and 57.14% of the first authors originated from the United States. Two main research themes were identified in this field: ChatGPT as a tool to assist teachers in preparing practicum sessions and analyzing ChatGPT’s ability to generate reports. The study also highlights opportunities for further research on ChatGPT’s capability to analyze practicum reports and evaluate practicum worksheet responses. This study provides a foundation for future researchers to identify topics and research gaps in the field.